Adaptive Relaying of Radial Distribution System with Distributed Generation - Murali Matcha; Sharath Kumar Papani; Vijetha Killamsetti (International Journal of Electrical and Computer Engineering (IJECE), 2013)
In this paper, the effect of DG penetration on the short circuit level has been studied in a distribution system.  The number of DG sources is increased to study the effect that these changes may have on the coordination of protective directional over-current relays (DOCR). The relays in the distribution system have to be coordinated so as to avoid mal-operation and unnecessary outage of healthy part of the system.  Results are compared to that of the normal case to investigate the impact of the DG on the short circuit currents of the network to deduce the effect on protective devices and some conclusions are documented. This paper presents the short circuit analysis of single phase to ground fault applied to simple radial distribution system and the corresponding Overcurrent relay coordination is presented using NEPLAN Software. Results obtained are verified by manual calculation.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2578